Records Surveys and the Management of Public Registry - Imana Harun, Zakira; Farik Mat Yatin, Saiful; Syahirah Mohamad Mobin, Noor; Norolazmi, Nurzeelawati; Atiqaf Mahathir, Nur; Nazir Ahmad, Mohd; Iza Ahmad Kamal, Jannatul (International Journal of Engineering and Technology, 2018)
This study investigates the role of records surveys in the management of public registry. The ultimate goal was to know how effective records surveys in enhancing records management practices in organizations. This study uses interview as an instrument to achieve the desired goals, to inculcate a sound record management practice in the public registry. Records surveys are a critical exercise aimed at achieving proper records management practices. This is because the amount of records in an organization is growing rapidly. Managing growth and the variety of content and location is a complex process. Records surveys are indispensable as a benchmark to make an effective records management practice.Â Â Â